Water vapor absorption spectroscopy and validation tests of databases in the far-infrared (50–720 cm-1). Part 1: Natural water. (November 2022) - Toureille, M.; Koroleva, A.O.; Mikhailenko, S.N.; Pirali, O.; Campargue, A.
Highlights: The far-infrared rotational spectrum of natural water vapor is studied by FTS with a synchrotron radiation source. 454 lines of the 2867 water lines measured in the 50–720 cm -1 region are observed for the first time by absorption spectroscopy. A few position deviations are noted compared to the HITRAN2020 and W2020 line lists. For H2 16 O, a better agreement is achieved with positions calculated using the effective Bending–Rotation Hamiltonian approach. Abstract: The rotational spectrum of water vapor in natural isotopic abundance has been recorded by high resolution (≈ 0.001 cm -1 ) Fourier transform spectroscopy at the AILES beam line of the SOLEIL synchrotron. The room temperature absorption spectrum has been recorded between 50 and 720 cm -1 using five pressure values up to 7 mbar and an absorption pathlength of 151.75 m. Line parameters were retrieved for the five recorded spectra and then combined in a global list of 2867 water lines with line intensity ranging between a few 10 –26 and 10 –19 cm/molecule. 454 of the measured lines are newly observed by absorption spectroscopy. The spectral calibration based on a statistical matching with about 700 accurate reference line positions allows for line center determinations with an accuracy of 5 × 10 –5 cm -1 for well isolated lines of intermediate intensity. The large spectral coverage, the achieved position accuracy and sensitivity of the constructed line list make it valuable for validation tests of the current spectroscopic databases. Six water isotopologues (H2 18 O, H2 16 O, H2 17 O, HD 18 O, HD 16 O, and HD 17 O) were found to contribute to the spectrum. The line position comparison to the recent HITRAN2020 spectroscopic database and to the W2020 line lists of H2 16 O, H2 17 O and H2 18 O, [Furtenbacher et al. J. Phys. Chem. Ref. Data 49 (2020) 043103; https://doi.org/10.1063/5.0030680] shows an overall very good agreement. Nevertheless, a number of significant deviations are observed. Part of them has an amplitude largely exceeding the W2020 claimed error bars. On the basis of the experimental data at disposal for the main isotopologue (1310 transitions), the best agreement is achieved with the positions calculated using the effective Bending–Rotation Hamiltonian [Coudert et al. J Mol Spectrosc 2014;303:36–41. https://doi.org/10.1016/j.jms.2014.07.003]. Graphical abstract: Image, graphical abstract